(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2019)
Introduction. Housing as a branch of the economy is intended to satisfy one of the rights declared by the Constitution of Ukraine - the right to own housing. The provision of such a right by the state is possible provided that an effective housing policy is developed and implemented. As a consequence, an effective housing ceiling will also promote the development of other related sectors of the economy. The purpose of the article is to provide a theoretical justification for the feasibility of using certain forms of lending in the practice of housing. Achieving this goal requires the following tasks: to systematize forms of crediting housing construction; to conduct an analysis of the state of housing construction in Ukraine and identify problems of its development; to identify the features of mortgage lending as a financing tool for housing construction. Results. The article deals with the peculiarities of such forms of credit financing of housing construction as a bond loan, bank lending and mortgage lending. The main advantages and disadvantages of using such forms of financing in the practice of construction of residential real estate have been identified. The trends of credit financing of housing construction in Ukraine during 2014 - 2018 have been established. The role of flow lending in housing finance has been identified, and bottlenecks in the development of mortgage lending in Ukraine have been identified. Conclusions. The use of borrowed resources as a source of housing finance has indisputable benefits, since it contributes primarily to the socio-economic development of the country and promotes the right of every citizen to own a home. However, when choosing a form of housing loan, it is advisable to be guided by the advantages and disadvantages of each individual form for a particular residential real estate object. The presence of identified problematic aspects in the housing finance system indicates the need for continuous study of the peculiarities of the application of separate sources of financing for the construction of residential real estate objects.